LOWER RATES OF EYE CARE UTILIZATION AMONG VISUALLY IMPAIRED SUBSIDIZED SENIOR HOUSING RESIDENTS. (11th November 2018) - Elliott, A; Heskett, M; McGwin Jr, G; Owsley, C
Abstract: The purpose of this study was to examine the rate of self-reported vision impairment and eye care utilization among residents of subsidized senior housing (SSH) communities. This was a cross-sectional, observational study. Residents of 12 SSH communities in Jefferson County, AL self-reported their vision status and eye care utilization as part of vision screening events held in their community. Results: 237 residents self-reported their vision status and eye care utilization. A third of participants (33.3%) reported difficulty with distance vision while 38% reported difficulty with near vision. Rates of eye disease among this sample were as follows: 40.3% reported having cataracts, 13.6% reported having glaucoma, 4.2% reported having age-related macular degeneration, and 5.5% reported having diabetic retinopathy. The majority of participants (52.8%) had not been to see an eye care provider within the last year. Persons with vision impairment were less likely to report having seen an eye care provider within the last year than those without impairment (p=0.03). This study presents the first self-reported findings regarding visual status and eye care utilization among socioeconomically disadvantaged older adults residing in SSH. Many residents reported vision difficulties and self-reported chronic eye diseases yet the majority had not visited an eye care provider within the last year. There is a need for health promotion and education in this population regarding eye care.